Nurses' and elderly patients’ perceptions regarding autonomy, privacy and informed consent in nursing interventions in Greece - Lemonidou, Chryssoula; Leino-Kilpi, Helena; Välimäki, Maritta; Dassen, Theo; Gasull, Maria; Scott, Philomena Anne; Papathanassoglou, Elizabeth; Arndt, Marianne; Merkouris, Anastasios (My University, 2002)
Ethics increasingly becomes a forefront issue in health care decision-making, as health care becomes more technologically and organizationally complex. Hence, a great number of new laws on the status and rights of patients and professional codes have been adopted in Europe. However, research suggests that violation of patients’ rights of autonomy, informed consent and privacy may still be common, especially in elderly care.